Pakistan - Tax Policy Report : Tapping Tax Bases for Development - Summary Report - World Bank (World Bank, 2012)
The main message of this report is that Pakistan can take measures to increase the tax to gross domestic product (GDP) ratio by around 3.5 percentage points over the next five years. In order to ensure a healthy long-run economic development, Pakistan needs to embrace substantial changes in tax policy aimed at increasing the buoyancy of the tax system, broadening the tax bases, reducing distortions and phasing out exemptions. Such tax reforms are also required to deal with the risks stemming from sustained large budget deficits. Failing to act sooner rather than later, only makes the problem more difficult to address without considerable instability, raises the probability of fiscal and financial disarray at some point in the future, and runs the risks of further constraining policy flexibility in future. This report highlights design ingredients for a comprehensive reform of tax policy in Pakistan. In the final analysis, the success of tax reform will depend less on the mechanism of taxation and more on the politics of taxation. Beyond adequate administrative resources and an implementation strategy, this will require a clear political recognition of the importance of the task and the willingness to persist with tax reform over the long haul.